Manajemen Bandwidth Menggunakan Metoda Queue Tree Studi Kasus Dinas Perpustakaan Dan Kearsipan Riau - Jason Prawira Azali; Dahliyusmanto Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Covid-19 is a global pandemic that has affected many jobs. Meetings that used to be held face-to-face are now being held online. The Riau Provincial Library and Archives Service (DIPERSIP) also implements online meetings, but this application is not supported by an adequate network configuration. This is evidenced by the results of the Quality of Services (QoS) measurement which get a poor score based on the TIPHON standard. To overcome this, a queue tree is applied to the DIPERSIP router to manage bandwidth usage. Configuration begins with creating static and dynamic address lists for conference meetings. Then create a mangle to mark connections and packets that are useful for the queue tree, and end with the creation of a queue tree to limit every activity related to upload-download. This configuration has proven to be effective in overcoming existing problems, as evidenced by the QoS re-measurement results that get very good scores.Keywords: Address List, Bandwidth, Mangle, Quality of Services (QOS) Queue Tree.